Generalized stochastic derivatives on spaces of nonregular generalized functions of Meixner white noise - Kachanovskii, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We introduce and study generalized stochastic derivatives on Kondratiev-type spaces of nonregular generalized functions of Meixner white noise. Properties of these derivatives are quite analogous to properties of stochastic derivatives in the Gaussian analysis. As an example, we calculate the generalized stochastic derivative of a solution of a stochastic equation with Wick-type nonlinearity.